Cooling performance of an impinging synthetic jet in a microchannel with nanofluids: An Eulerian approach. (April 2021) - Lau, G.E.; Mohammadpour, J.; Lee, A.
Highlights: Heat transfer of synthetic jet microchannel is enhanced with nanofluids. Thermal conductivity and convection affect overall thermal performance. Vortex formation and flow disturbance are vital in enhancing convective heat transfer. Al2 O3 -water shows 38% improvement in the overall thermal performance. Abstract: Numerical investigations of heat transfer enhancement in a three-dimensional micro-channel with a single synthetic jet were conducted using Al2 O3 -water, CuO-water and TiO2 -water nanofluids. The effects of different types of nanoparticles at particle volume concentrations of 1%, 2% and 5% on the thermal performance in the micro-channel were examined. The numerical tool was validated against existing experimental data on the heat transfer characteristic of nanofluids in micro-channel. Heat transfer enhancement using nanofluids based on the Eulerian single-phase model was assessed for the cases with and without the operation of the synthetic jet. In general, the overall thermal performance was greatly influenced by the thermal conductivity and dynamic viscosity of the working nanofluids. The former corresponds to thermal enhancement by conduction whilst the latter corresponds to convective enhancement due to the periodic oscillation of the synthetic jet diaphragm. As the particle volume concentration of a nanofluid increased, effectiveness of the synthetic jet to provide convective cooling became poorer on account of higher viscosity. Nevertheless, in some cases, this can be overcome by the enhancement in thermal conductivity, depending on the Peclet number of the working fluid. Synthetic jet microchannel with Al2 O3 -water nanofluid at φ = 5% showed the best overall cooling performance whereas TiO2 -water nanofluid at φ = 5% failed to improve the thermal performance.